Quand les toiles d'araignées s'unissent, elles peuvent entraver un lion - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Quand les toiles d'araignées s'unissent, elles peuvent entraver un lion'Proverbe éthiopien